The Effectiveness of STAD Learning Model towards Mathematics Subject Learning Achievement students of State Elementary School (Joyful Learning Journal, 2017)
Abstrak Pembelajaran dikatakan efektif apabila peserta didik mendapatkan hasil maksimal. Hasil belajar siswa pada mata pelajaran Matematika di SDN Gugus Ki Hajar Dewantara belum mencapai KKM. Hal ini dipengaruhi oleh siswa kurang antusias terhadap pelajaran matematika dan media yang digunakan kurang bervariasi hanya menggunakan media gambar. Hasil belajar maksimal dapat diperoleh melalui salah satu model pembelajaran STAD dengan sistem belajar kelompok dan media benda konkret untuk mempermudah memahami materi. Tujuan dari penelitian ini yaitu menguji model pembelajaran pembelajaran STAD dengan media benda konkret lebih efektif daripada menggunakan model pembelajaran TAI. Hasil penelitian uji z menunjukkan z hitung=8,3â‰¥ z tabel = 1,645 bahwa hasil belajar siswa dengan model pembelajaran STAD dapat mencapai Kriteria Ketuntasan Minimal (KKM). Hasil uji-t menunjukkan nilai thitung>ttabel, t hitung = 9,1026 dan t tabel = 1,684 bahwa model pembelajaran STAD lebih efektif terhadap hasil belajar Matematika siswa kelas V SDN Gugus Ki Hajar Dewantara Kabupaten Sragen. ______________________________________________________________ Abstract ___________________________________________________________________ Learning is said to be effective when students get maximum result. However, it was found that the mathematics subject learning achievement of the students of SDN Cluster Ki Hajar Dewantara had not passed the passing grade (KKM) yet. This was influenced by the less enthusiastic students in joining the mathematics class and the less variative media used, in this case the teacher only used picture media. One way to maximize students' learning achievement is by using STAD learning model with the system of group learning and concrete objects to ease students' materials understanding. This study was aimed at examining the effectiveness of the use of STAD learning model with the media concrete objects towards mathematics subject learning achievement of the fifth grade students of SDN Cluster Ki Hajar Dewantara, Sragen and examining STAD learning model with the media of concrete objects against TAI learning model. The findings showed that STAD learning model was more effective towards students' activities z count = 8,3â‰¥ z table = 1,. It was proven by the results of t-test which presented that the values of tcount>ttable t hitung = 9,1026 dan t tabel = 1,684. In other words, STAD learning model is more effective towards mathematics subject learnin achievement of the fifth grade students of SDN Cluster Ki Hajar Dewantara, Sragen Regency.